Chinese foreign investment laws recent developments towards a market economy - Zeng, Huaqun (East Asian Institute (EAI) contemporary China series, 1999)
"Since 1993, Chinese foreign investment laws (CFILs) have been moving towards the common principles of foreign investment laws in market economies.This volume summarises four features of the common principles and surveys four aspects of recent developments of CFILs towards these principles — namely, expanding the economic sectors for foreign direct investment (FDI), allowing multiple forms or types of FDI, granting national treatment of FDI step by step, and pursuing transparency of CFILs; and finally comments on the significance of recent developments of CFILs.The author points out that recent developments of CFILs towards a common approach have made great positive impacts on FDI to China, treatment of FDI in China and structural adjustment of CFILs."